Model Eksplanatori Sawan Mayit dan Proses Pencarian Perawatan dalam Masyarakat Mayong, Jepara - Romadhonia, Fadhila Nurul Laili; Husain, Fadly (Aceh Anthropological Journal, 2025)
Sawan mayit is a Javanese illness associated with death. This article aims to examine the explanatory model of sawan mayit and explore the care-seeking process by sawan mayit sufferers and family caregivers in Mayong, Jepara. The research method used was descriptive-qualitative with data collection techniques through documentation, participatory observation, and in-depth interviews. Data analysis included data reduction, data presentation, and conclusion drawing. The exploratory model represents the local knowledge system of the Mayong community regarding sawan mayit through five conceptual frameworks, namely etiology, onset of symptoms, pathophysiology, course of illness, and treatment. The results of the analysis show that sawan mayit is understood and explained as a disorder of bodily functions after experiencing a series of death-related experiences. Common symptoms include fever, dizziness, weakness, sleep disturbances, and emotional disturbances such as fear and anxiety. The mechanism of sawan mayit is explained through the concept of medical syncretism, which combines biomedical concepts and traditional beliefs. Sawan mayit not only affect the physical and emotional aspects, but also affect the social aspects of the sufferer. There are dynamics in the process of seeking sawan mayit treatment, which uses three sectors of health care: the popular sector, the professional sector, and the traditional sector. The explanation and understanding of sawan mayit not only affect the labeling process of the illness, but also the care-seeking process.Abstrak: Sawan mayit adalah penyakit dalam kepercayaan masyarakat Jawa yang dikaitkan dengan peristiwa kematian. Artikel ini bertujuan untuk mengkaji model eksplanatori masyarakat Mayong, Jepara mengenai sawan mayit serta mengeksplorasi proses pencarian perawatan oleh penderita sawan mayit. Metode penelitian menggunakan kualitatif deskriptif dengan teknik pengumpulan data melalui dokumentasi, observasi partisipatif, dan wawancara mendalam. Analisis data meliputi reduksi data, penyajian data, dan pengambilan kesimpulan. Model eksplanaori merepresentasikan sistem pengetahuan lokal masyarakat Mayong mengenai sawan mayit melalui lima kerangka konsep yaitu etiologi, gejala, patofisiologi, perjalanan penyakit, dan perawatan. Hasil analisis menunjukkan bahwa sawan mayit dipahami dan dijelaskan sebagai gangguan fungsi tubuh setelah mengalami serangkaian pengalaman berkaitan dengan kematian. Gejala umum meliputi demam, pusing, lemas, gangguan tidur, hingga gangguan emosional seperti ketakutan dan cemas. Adapun mekanisme terjadinya sawan mayit dijelaskan melalui konsep sinkretisme medis yang menggabungkan konsep biomedis dan kepercayaan tradisional. Sawan mayit tidak hanya berdampak pada aspek fisik dan emosional, tetapi juga memengaruhi aspek sosial penderitanya. Terdapat dinamika dalam proses pencarian perawatan sawan mayit yang menggunakan tiga sektor perawatan yaitu sektor populer, sektor profesional, dan sektor tradisional. Penjelasan dan pemahaman mengenai sawan mayit tidak hanya memengaruhi proses pemberian label terhadap penyakit, tetapi juga proses pencarian perawatan.